Synthesis of a Novel Single-Source Precursor for the Production of Lead Chalcogenide Thin Films - Nathaniel Owusu Boadi; Selina Ama Saah; Johannes A. M. Awudza (Journal of Chemistry)
A novel complex [Pb((SePiPr2)2N) (S2CNEt2)] has been synthesized and characterized by microelemental analysis, melting point NMR, and FT-IR spectroscopies. Its crystal structure has also been successfully determined using single-crystal X-ray crystallography. The structure indicates a distorted square pyramidal geometry with the four basal atoms being noncoplanar. The complex was used as a single-source precursor for the deposition of lead chalcogenide thin films on glass substrates at 300, 350, 400, and 450°C by AACVD. The films were characterized by SEM, EDX, and XRD. The XRD peaks matched with cubic PbSe at all temperatures. The SEM micrographs showed the formation of cubes with the lower temperatures (300–350°C) showing well-resolved cubes while with the higher temperatures (400–450°C) showing poorly resolved cubes. The EDX analyses confirmed the formation of PbSe thin films at all the deposition temperatures.